TESTING FOREIGN LANGUAGE PROFICIENCY – WHAT VERBAL PROTOCOLS REVEAL - Medved Krajnović, Marta (Array, 2007)
The paper deals with several issues related to testing second language learners’ communicative language competence. It concentrates on verbal protocols as a means of gaining insight into learners’ test taking strategies and cognitive processes, and as one of the ways of checking test validity and reliability. The research part of the paper presents results of the application of the verbal protocol technique with primary school children who were faced with three different cloze-test tasks. The research proved that verbal protocols can be used with learners of this age group, and that the application of verbal protocols is very important for a more reliable interpretation of learners’ test results.